2013
DOI: 10.1159/000353177
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Asymmetry of Humeral Torsion and Length in African Apes and Humans

Abstract: Few studies have directly compared human and African ape upper limb skeletal asymmetries despite the potential such comparisons have for understanding the origins of functional lateralization in humans and non-human primates. Here, we report the magnitude and direction of asymmetries in humeral torsion and humeral length in paired humeri of 40 Gorilla gorilla, 40 Pan troglodytes and 40 Homo sapiens. We test whether absolute and directional asymmetries differ between measurements, species and sexes. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 106 publications
(132 reference statements)
2
5
2
Order By: Relevance
“…11&12). Our study therefore contradicted the report of Barros and Soligo (2013) which stated that both the magnitude and direction of asymmetries in humeral torsion in paired humeri from humans are unique in being lateralized to the right. However, in all the parameters measured in this study, we observed that right humerus in both sexes in most cases presented larger values compared with the left except the angle of torsion which is variable.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…11&12). Our study therefore contradicted the report of Barros and Soligo (2013) which stated that both the magnitude and direction of asymmetries in humeral torsion in paired humeri from humans are unique in being lateralized to the right. However, in all the parameters measured in this study, we observed that right humerus in both sexes in most cases presented larger values compared with the left except the angle of torsion which is variable.…”
Section: Discussioncontrasting
confidence: 99%
“…7&8). This observation in humeral length is in agreement with the report of Cuk et al, (2001) and Barros & Soligo (2013) which showed that average lateral asymmetry in the arms was to the right and that humans are unique in being lateralized to the right. Looking at the measurement of the mid-shaft circumference (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Following this model, biomechanical studies focusing on variation in osseous tissue have advanced our understanding of the interrelationships among habitual behavior, locomotion, and loading environments for extant (Fajardo & Müller, ; Marchi, ; Ryan & Ketcham, ; Ryan & Krovitz, ; Ryan & van Rietbergen, ; Ryan & Walker, ; Stock & Pfeiffer, ) and extinct primates (Barak et al, ; Ryan & Ketcham, ; Trinkaus, Churchill, & Ruff, ). Studies applying this perspective to questions of hand preference frequently report a right directional asymmetry in mechanical resistance of the upper limbs (Barros & Soligo, ; Churchill & Formicola, ; Macintosh, Pinhasi, & Stock, ; Shaw, Hofmann, Petraglia, Stock, & Gottschall, ; Trinkaus et al, ) and manual remains (Lazenby, ; Lazenby, Cooper, Angus, & Hallgrimsson, ; Mays, ; Roy, Ruff, & Plato, ; Singh, ) of past human populations that are commensurate with group/species‐level right handedness. Such departures from right/left symmetry are thought to be the byproduct of frequent lateralized loading on the dominant side (Auerbach & Ruff, ; Kanchan, Mohan Kumar, Pradeep Kumar, & Yoganarasimha, ), which is supported by studies of uni‐manual loading and self‐reported hand preference in living athletes (Bass et al, ; Shaw, ).…”
Section: The Evolution Of Hand Preference and Handednessmentioning
confidence: 99%
“…4%) actually possessed a full suite of morphometric right-handed characters, the majority of right-handed individuals possessed varying combinations of right-handed characters, reverse righthanded characters, and indeterminate features in different proportions. The variability in composition of bilateral asymmetries within an individual and between individuals that is shown in our study suggests that the biomechanical causes of asymmetries are complex, affecting each bony feature in each individual in a different way (Auerbach and Ruff, 2006;Barros and Soligo, 2013;Cashmore and Zakrzewski, 2013). This variability is likely due to a variety of underlying causes, such as idiosyncratic behaviors, occupations that require habitual postures (e.g., the stoop of a dentist or the forward head posture of a data entry specialist or microscopist) or repetitive movements (e.g., the throwing of baseballs by a pitcher or the throwing of pots by a ceramicist; (see also Pieper, 1998;Murachovsky et al, 2010;Wyland, 2012), besides variations in the morphology and location of muscle attachments due to genetic and epigenetic causes.…”
Section: Right-handed Versus Left-handed Charactersmentioning
confidence: 74%
“…This means that any standard statistical tests need to be supplemented by an analysis, such as ours, that retains the functional coherence of the features of an apparatus of each individual. Other studies have also remarked on the need for population‐level analyses to be supplemented by analyses at the individual level (e.g., Rhodes, ; Barros and Soligo, ).…”
Section: Discussionmentioning
confidence: 99%